2019
DOI: 10.1111/pedi.12928
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and self‐rated health among ethnically diverse adolescents with type 1 diabetes

Abstract: Objective: Patient-reported outcomes have received increased attention as treatment outcomes and indicators of wellbeing. A1c has been criticized as lacking patient-centered relevance because individuals are often unaware of their A1c, and studies also often fail to show a benefit of intensive control on quality of life. The goal of the present study was to examine self-rated health (SRH) in relation to diabetes self-care behaviors, socioeconomic factors, treatment regimen characteristics, and glycemic control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Recently diagnosed patients [ 74 ] • Children (age 8–13) showed elevated levels of depression at diagnosis which significantly decreased 12 months after diagnosis. Self-Care Inventory-Revised (SCI-R) [ 36 , 57 , 62 , 69 ] Perceived adherence to self-care regimen • Children who accept their diabetes diagnosis and integrate within their self-identity were more confident and showed better self-care. • Patients who use an insulin pump showed better self-care than patients who use injectables.…”
Section: Resultsmentioning
confidence: 99%
“…Recently diagnosed patients [ 74 ] • Children (age 8–13) showed elevated levels of depression at diagnosis which significantly decreased 12 months after diagnosis. Self-Care Inventory-Revised (SCI-R) [ 36 , 57 , 62 , 69 ] Perceived adherence to self-care regimen • Children who accept their diabetes diagnosis and integrate within their self-identity were more confident and showed better self-care. • Patients who use an insulin pump showed better self-care than patients who use injectables.…”
Section: Resultsmentioning
confidence: 99%
“…We further found that a higher self-rated health status was associated with less frequent monitoring of blood glucose, although such association was attenuated after adjustment. It is possible that the motivation to perform blood glucose monitoring is largely influenced by the perceived concern on disease progression [ 31 ], and thus a poor self-rated health status was often associated with higher HbA1c levels [ 32 , 33 ]. Therefore, frequent monitoring of blood glucose among patients with poor self-rated health status may be explained by the fear of adverse consequences of diabetic hyperosmolar syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Model 1 was adjusted for variables including child age, gender, disease duration, insulin regimen, daily blood glucose monitoring, and self-management level that demonstrated a correlation with pediatric glycaemic control in previous studies ( 28 , 29 ). For example, insulin pump therapy, higher adherence for blood glucose monitoring, and better self-management were associated with lower HbA1c ( 30 ). Model 2 was adjusted for variables in Model 1 plus parental depressive symptoms and diabetes distress.…”
Section: Methodsmentioning
confidence: 99%